Integrando tecnologias educacionais e a Teoria Antropológica do Didático: Uma abordagem para o ensino de movimento circular no ensino médio - Aparecido, Alexandre Jurandir (2023)
The evaluation of the cycle path structure to consider the viability of the bicycle as an alternative for urban transport materialized the paradigm of questioning the world, the basis of the Anthropological Theory of Didactics, which guides this work. In this direction, we present a didactic sequence for teaching circular motion, structured through educational technologies, especially Microsoft, carried out with the first year of high school at a school in Franca/SP. Establishing the questioning of the world, the introduction and institutionalization of concepts, research and transdisciplinarity as some pillars of support, the instructional design was implemented by conceiving tasks that configure the didactic situations in which students learn through the mobilization of knowledge. In the design and application of the assignments, the Theory of Didactic Situations was a fruitful tool both in structuring and as an element of analysis. We present the results of applying the didactic sequence, with the students' performance in carrying out assignments such as the design and manufacture of transmission systems at FABLAB. We demonstrate how educational technologies can reinforce the didactic contract and enable a more efficient management of activities. Among educational technologies, Teams played a central role serving as a virtual learning environment, along with Onenote as a digital notebook. As an educational product of this work, we developed a plot in Sway, entitled “Teaching Circular Movement with Microsoft Technologies”, which presents the didactic sequence and narrates the experience of its application by the author and at the same time shares guidance texts and other diverse digital materials for the reproduction/adaptation of the didactic sequence by other teachers.